Revolución y ganadería en el Norte de México - Lopes, Maria Aparecida De S. [UNESP] (My University, 2008)
Through the analysis of Mexican livestock statistics and Sonora and Chihuahua regional census, this work discusses the condition of livestock farming in Northern Mexico during the first decades of the twentieth century, specially after the Revolution. There is no doubt that during this period, the absolute number of livestock heads diminished throughout Mexico, but estate depredations did vary geographically. In Nortehrn Mexico, livestock farming suffered more in Chihuahua than in Sonora, and herd recovery was also faster in Sonora. This analysis also allows us to underscore the role of postrevolutionary elites in rebuilding regional economies during the 1920's.
Revolution and livestock farming in Northern Mexico